PERAN IBADAH DAN KESEHATAN DALAM MEMBANGUN KELUARGA SAKINAH, MAWADDAH WA RAHMAH DI ERA MODERN - Adellia Pirtika Putri Lubis; Anin Ramaida; Elma Kencana; Firly Rahmadani; Nadya; Nazwa Afrilia; Safvhira Rahma Rosalia; Sintya; Ahlun Nazi Siregar (PT. Hasba Edukasi Mandiri, 2026)
Family is the smallest social unit that serves as the fundamental foundation in the structure and dynamics of social, national, and state life. However, in the current modern era, families face various significant challenges. This article explains the concept of family, the role of worship, and the importance of maintaining health, as well as how both are interrelated in building households that embody the values of Sakinah, Mawaddah wa Rahmah in the modern era. This study uses a literature review method as its primary basis. Establishing a sakinah, mawaddah, and rahmah household is indeed a tangible form of continuous worship. Achieving an ideal family is inseparable from an understanding of the comprehensive concept of health. In the family context, health is an absolute prerequisite for every family member to carry out their roles, obligations, and worship optimally. Worship and health are two inseparable aspects that complement each other in building a complete and harmonious family foundation.